Antimicrobial Efficacy of an Atmospheric Pressure Plasma Jet Against Biofilms of Pseudomonas aeruginosa and Staphylococcus epidermidis. Issue 2 (1st October 2012) - Matthes, Rutger; Koban, Ina; Bender, Claudia; Masur, Kai; Kindel, Eckhard; Weltmann, Klaus‐Dieter; Kocher, Thomas; Kramer, Axel; Hübner, Nils‐Olaf
Abstract Microbial biofilms impair wound healing and the efficacy of antiseptics. This study used the plasma source kinpen 09 to investigate the efficacy of argon and an argon/oxygen‐mixture plasma against in vitro biofilms of Pseudomonas aeruginosa and Staphylococcus epidermidis compared to the antiseptic chlorhexidine digluconate (CHX). Biofilms were treated for 30, 60, 150, or 300 s with plasma and for 600 s with a 0.1% CHX solution. Thereafter, the biofilms were dispersed and their inactivation was determined as the reduction of colony forming units. Plasma treatment led to a significant antimicrobial effect compared to the untreated control and was at least as effective as the treatment with CHX, or even better, depending on the gas admixture, the bacterial strain used, and the exposure time. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>